Bioorganic fertilizers from agricultural waste enhance rice growth under saline soil conditions - Nuntavun Riddech; Piyada Theerakulpisut; Yen Nhi Ma; Pornrapee Sarin (Scientific Reports)
Abstract Agricultural waste (AW) presents significant environmental challenges if not effectively managed. Recycling AW as bio-organic fertilizers (BIOs) offers a sustainable solution, improving soil health, reducing dependence on chemical fertilizers, and stimulating crop growth. This study investigated the effectiveness of BIOs generated from AW composted with plant growth-promoting rhizobacteria (PGPR), including Enterobacter sp. R24, Bacillus tequilensis P8, and Pseudomonas azotoformans S81. BIOs produced from peanut shell, rice straw, duckweed, and rice bran were applied to rice seedlings under normal and saline (85 mM NaCl) conditions. The results revealed that PGPR-fermented BIOs utilized for only 15–30 days significantly improved seed germination and root length. BIO-duckweed and BIO-peanut proved high in nitrogen, phosphate, and potassium content, thereby increasing total biomass by 188% and 85%, respectively. In non-saline soil, BIO-peanut shell outperformed chemical fertilizers, promoting root growth and chlorophyll content. Additionally, BIO-rice straw gave a 58% reduction in proline levels under saline conditions, indicating stress reduction capacity. BIOs treatments demonstrated significant improvements in both nutrient availability and microbial diversity. Specifically, BIO-peanut shell and BIO-duckweed increased phosphate availability in soil by 143.26%, 13.80% over control soil and 7.23%, 30.69% over chemical treatment, respectively. The denaturing gradient gel electrophoresis (DGGE) analysis further revealed a noticeable increase in microbial diversity in soils treated with BIOs, which was absent in untreated soil. Indeed, BIO-rice straw promoted the development of five distinct bacterial genera in saline condition, underscoring BIOs’ ability to enhance the microbial community structure. The study highlights the potential of BIOs from AW combined with PGPRs to enhance rice growth under extreme salt stress. This sustainable alternative to chemical fertilizers enhances soil health by increasing nutrient availability, microbial diversity, and promoting beneficial soil microbes, ultimately improving long-term soil resilience and fertility.